Genetic Disruption of KLF1 K74 SUMOylation in Hematopoietic System Promotes Healthy Longevity in Mice. Issue 25 (13th July 2022) - Shyu, Yu‐Chiau; Liao, Po‐Cheng; Huang, Ting‐Shou; Yang, Chun‐Ju; Lu, Mu‐Jie; Huang, Shih‐Ming; Lin, Xin‐Yu; Liou, Cai‐Cin; Kao, Yu‐Hsiang; Lu, Chi‐Huan; Peng, Hui‐Ling; Chen, Jim‐Ray; et al.
Abstract: The quest for rejuvenation and prolonged lifespan through transfusion of young blood has been studied for decades with the hope of unlocking the mystery of the key substance(s) that exists in the circulating blood of juvenile organisms. However, a pivotal mediator has yet been identified. Here, atypical findings are presented that are observed in a knockin mouse model carrying a lysine to arginine substitution at residue 74 of Krüppel‐like factor 1 (KLF1/EKLF), the SUMOylation‐deficient Klf1 K74R/K74R mouse, that displayed significant improvement in geriatric disorders and lifespan extension. Klf1 K74R/K74R mice exhibit a marked delay in age‐related physical performance decline and disease progression as evidenced by physiological and pathological examinations. Furthermore, the KLF1(K74R) knockin affects a subset of lymphoid lineage cells; the abundance of tumor infiltrating effector CD8 + T cells and NKT cells is increased resulting in antitumor immune enhancement in response to tumor cell administration. Significantly, infusion of hematopoietic stem cells (HSCs) from Klf1 K74R/K74R mice extends the lifespan of the wild‐type mice. The Klf1 K74R/K74R mice appear to be an ideal animal model system for further understanding of the molecular/cellular basis of aging and development of new strategies for antiaging and prevention/treatment of age‐related diseases thus extending the healthspan as well as lifespan. Abstract : The quest for prolonged lifespan has been ongoing for decades with the hope of unlocking the mystery of the key substance(s) in longevity. This study presents a longevity mouse model that significantly improves geriatric disorders and lifespan in a hematopoietic manner. This animal model is invaluable for exploring new approaches for antiaging and offers a contribution to advancing geroscience.